Sex Differences in Type 2 Diabetes Mellitus-Related Left Ventricular Remodeling: A Cardiovascular Magnetic Resonance Study - Yongning Shang; Yulin Zhang; Weiling Leng; Xiaotian Lei; Liu Chen; Xiaoyue Zhou; Ziwen Liang; Jian Wang (Journal of Diabetes Research)
Background. The purpose of this study was to evaluate the sex differences in myocardial structure, tissue characteristics, and myocardial function in type 2 diabetes mellitus (T2DM) patients. Methods. A total of 62 T2DM patients and 40 controls were prospectively recruited for the study. All the participants were scanned using cardiovascular magnetic resonance (CMR) cine and underwent native and postcontrast T1 mapping to obtain left ventricular (LV) structure, function, and tissue characteristics. The differences between the control and T2DM patients were compared in males and females, respectively. Results. For myocardial structure, T2DM was associated with a larger ratio of myocardial mass to end-diastolic volume (MVR, T2DM: 0.87±0.20 vs. controls: 0.73±0.14, p=0.008) and thicker wall thickness (WT, T2DM: 6.5±1.1 mm vs. controls: 5.6±1.0 mm, p=0.002) in females. For tissue characteristics, T2DM was associated with a similar T1 value, elevated extracellular volume fraction (ECV, T2DM: 27.8±3.6% vs. controls: 25.1±2.5%, p=0.002), and increased extracellular matrix volume index (ECMVi, T2DM: 15.8±3.8 ml/m2 vs. controls: 13.4±2.7 ml/m2, p=0.008) in males. For myocardial function, in male, compared with control, T2DM was associated with decreased peak longitudinal diastolic strain rate (PLDSR, T2DM: 0.97±0.19 1/s vs. control: 1.13±0.29 1/s, p=0.030). Conclusions. There might be sex differences in myocardial remodeling induced by T2DM, including LV structural concentric remodeling in female patients and extracellular matrix remodeling and subclinical diastolic dysfunction in male patients.